Vlt/Eris Observations of the v960 Mon System: A Dust-Embedded Substellar Object Formed by Gravitational Instability? - Perez-Marquez, S; Weber, P (American Astronomical Society, 2025)
V960 Mon is an FU Orionis object that shows strong evidence of a gravitationally unstable spiral arm that is fragmenting into several dust clumps. We report the discovery of a new substellar companion candidate around this young star, identified in high-contrast L ′ -band imaging with Very Large Telescope/Enhanced Resolution Imager and Spectrograph. The object is detected at a projected separation of 0 . ″ 898 ± 0 . ″ 01 with a contrast of (8.39 ± 0.07) × 10−3. The candidate lies close to the clumps previously detected in the submillimeter (at 1.3 mm) and is co-located with extended polarized IR signal from scattered stellar irradiation, suggesting it is deeply embedded. The object is undetected in the SPHERE H-band total intensity, placing an upper mass limit of ∼38 MJup from the contrast curve. Using evolutionary models at an assumed age of 1 Myr, we estimate a mass of ∼660 MJup from the L′ brightness; however, this value likely includes a significant contribution from a disk around the companion. The discrepancy between near- and mid-infrared results again suggests the source is deeply embedded in dust. This candidate may represent an actively accreting, disk-bearing substellar object in a young, gravitationally unstable environment. © 2025. The Author(s). Published by the American Astronomical Society.